Interstitial Cells in the Pineal Gland of Pregnant and Nonpregnant Viscachas (Lagostomus maximus maximus): A Morphometric and Biochemical Study - Busolini, Fabricio Iván (2018)
The pineal gland of mammals undergoes morphological and biochemical changes throughout the gestation period. In viscachas, a seasonal breeding rodent, pregnancy lasts approximately 154 days and 3 stages can be defined, i.e., early, mid, and late pregnancy. The purpose of this study is to analyze morphometric variations in the expression of S-100 protein, glial fibrillary acidic protein (GFAP), and vimentin in the interstitial cells (IC) in pregnant and nonpregnant viscachas by immunohistochemistry (IHC). We also aim to evaluate a probable relation between glandular activity and pregnancy. The immunopositive percentage area (%IA) for the studied proteins and the number of immunoreactive cells against the S-100 protein with a visible nucleus (n IC-S-100) were analyzed. Estradiol and progesterone serum levels were also determined by RIA. Variations in the expression of the S-100 protein and GFAP, as well as changes in the n IC-S-100 related to serum hormone levels, were found between pregnant and nonpregnant viscachas. Viscachas in mid pregnancy exhibited the highest values of %IA for the analyzed proteins, followed by females in late and early pregnancy, while the nonpregnant ones showed the lowest values for all of the groups studied. Likewise, the n IC-S-100 also varied following the same pattern. Thus, these variations seem to indicate a direct relationship between glandular activity and gonadal hormone levels. On these grounds, we may conclude that IC undergo changes in relation to ovarian hormone levels and participate in the regulation of glandular activity during pregnancy. However, further research is necessary to elucidate this relationship.